Comparison of copper and aluminum doped cobalt ferrate nanoparticles for improving biohydrogen production. (January 2022) - Li, Wenqing; Zhang, Jishi; Yang, Junwei; Zhang, Junchu; Li, Zhenmin; Yang, Yunjun; Zang, Lihua
Graphical abstract: Highlights: CoAl0.2 Fe1.8 O4 and CoCu0.2 Fe1.8 O4 NPs were synthesized to raise bioH2 yield. Humic acids were reduced by addition of CoAl0.2 Fe1.8 O4 or CoCu0.2 Fe1.8 O4 NPs. CoAl0.2 Fe1.8 O4 acted on cell membrane while CoCu0.2 Fe1.8 O4 acted on EPS. CoCu0.2 Fe1.8 O4 obtained Clostridium_sensu_stricto_1 more than CoAl0.2 Fe1.8 O4 . CoCu0.2 Fe1.8 O4 NPs improved H2 yield more than CoAl0.2 Fe1.8 O4 NPs. Abstract: Two various materials, copper and aluminum doped cobalt ferrite nanoparticles (NPs) were fabricated for investigating their effects of addition amounts on hydrogen (H2 ) synthesis and process stability. CoCu0.2 Fe1.8 O4 NPs enhanced H2 production more than CoAl0.2 Fe1.8 O4 NPs under same condition. The highest H2 yield of 212.25 ml/g glucose was found at optimal dosage of 300 mg/L CoCu0.2 Fe1.8 O4 NPs, revealing the increases of 43.17% and 6.67% compared with the control without NPs and 300 mg/L CoAl0.2 Fe1.8 O4 NPs groups, respectively. NPs level of more than 400 mg/L inhibited H2 generation. Further investigations illustrated that CoCu0.2 Fe1.8 O4 NPs were mainly distributed on extracellular polymer substance while CoAl0.2 Fe1.8 O4 NPs were mostly enriched on cell membrane, which facilitated electron transfer behavior. Community structure composition demonstrated that CoCu0.2 Fe1.8 O4 and CoAl0.2 Fe1.8 O4 separately caused a 9.67% and 9.03% increase in Clostridium sensu stricto 1 compared with the control reactor without NPs exposure.